Mixture composition and coal size effect on coal water mixture quality - Bazlina Dawami Afrah; Lia Cundari; Ni'matul Hakiki Vebri Awan; Illovine Hadassa; Eva Oktarinasari; Miftahurrizka Afrah (Chemical Engineering Department, Faculty of Engineering, Universitas Sriwijaya in collaboration with Asosiasi Pendidikan Tinggi Teknik Kimia Indonesia (APTEKIM), 2024)
Coal usage as a primary energy source is targeted to continue to increase and replace petroleum as the main energy source. Further processing is required to achieve the standard fuel characteristics, one of which is through a process called Coal Water Mixture (CWM) by adding water and additives to coal to produce fuel with characteristics like heavy oil. This research was conducted to analyze the best composition and size of the coal for CWM processing using variations in coal composition (20 %; 30 %; 40 %; 50 %; and 60 %) and coal particle size (40, 80, and 120 mesh). The parameters studied for each CWM product are product quantity, inherent moisture, density, pH, and calorific value. The results of the initial analysis show that the CWM product with a coal composition of 50 % has characteristics that most closely resemble Heavy Fuel Oil (HFO). CWM product with a coal composition of 50 % with all three variations of coal size was then tested for its calorific value and the respective values ​​were 3476.3153 cal/g; 4025.5551 cal/g; and 4488.4248 cal/g. The resulting product meets the physical characteristics qualifications, but to substitute HFO as fuel, it is necessary to use high quality coal, namely anthracite with a higher calorific value or upgrade the coal raw materials that will be used for the CWM processing.